∫xex(1+x)2dx is equal to 

xex(1+x)2dx is equal to 

  1. A

    ex1+x+C

  2. B

    11+x+C

  3. C

    ex(1+x)+C

  4. D

    ex(1+x)2+C

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    Let I=xex(1+x)2dx=ex(x+1)1(1+x)2dx=ex1(1+x)1(1+x)2dx

    Let f(x)=11+xf(x)=1(1+x)2

    we know that exf(x)+f(x)dx=exf(x)

     I=ex11+x1(1+x)2dx=ex1+x+C

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.